A systematic review of medication administration errors with transdermal patches - Lampert, Anette; Seiberth, Jasmin; Haefeli, Walter E.; Seidling, Hanna (Expert opinion on drug safety, 2014)
Transdermal patches provide an attractive route of drug delivery with considerable advantages over other routes of administration, for example maintenance of constant plasma drug levels and convenient usage. However, medication administration errors abound with this dosage form and frequently result in harm or treatment failure.
Gesehen am 15.10.2019